De-silencing the Past: Postmemory and Reparative Writing in Selected Works by African-American Women Writers - Orquídea Moreira Ribeiro (Ex Aequo: Revista da Associação Portuguesa de Estudos sobre as Mulheres)
Marianne Hirsch’s concept of postmemory implies a connection with the past that is indirect, mediated by the imagination and desire, transmitted to descendants or generations that have no memory of the traumatic event, but it can also entail a possible yearning to reconnect with the historical past as testimony, remembering and collective memory. This article focuses on this reconnection with the past with the aim of reading, questioning and analyzing traumatic memories of times past in selected works by four nineteenth and twentieth-century African American women writers (Harriet Jacobs, Zora Neale Hurston, Gayl Jones, and Toni Morrison) whose texts and characters carry the burden of traumatic memories and the will to share postmemories.